Cyberlaw and Data Protection Law - Zulhuda, Sonny (2016)
Cyberlaw covers a myriad of issues including private and public issues. Commerce and trade benefit a lot from the existence of cyberlaw and data protection law. It is pertinent for law students today to understand the nature and infrastructure of cyberspace generally and to analyse how legal questions arise from the context.